Singing Together, Yet Apart: The Experience of UK Choir Members and Facilitators During the Covid-19 Pandemic - Daffern, Helena; Balmer, Kelly; Brereton, Jude (Frontiers in Psychology, 2021)
The Covid-19 induced UK-wide lockdown in 2020 saw choirs face a unique situation of trying to continue without being able to meet in-person. Live networked simultaneous music-making for large groups of singers is not possible, so other ‘virtual choir’ activities were explored. A cross sectional online survey of 3948 choir members and facilitators from across the UK was conducted, with qualitative analysis of open text questions, to investigate which virtual choir solutions have been employed, how choir members and facilitators experience these in comparison to an ‘in-person’ choir, and whether the limitations and opportunities of virtual choir solutions shed light on the value of the experience of group singing as a whole. Three virtual choir models were employed: Multi-track, whereby individuals record a solo which is mixed into a choral soundtrack; Live streamed, where individuals take part in sessions streamed live over social media; Live tele-conferencing, for spoken interaction and/or singing using tele- conferencing software. Six themes were identified in the open text responses: Participation Practicalities, encompassing reactions to logistics of virtual models; Choir Continuity, reflecting the responsibility felt to maintain choir activities somehow; Wellbeing, with lockdown highlighting to many the importance of in- person choirs to their sense of wellbeing; Social Aspects, reflecting a sense of community and social identity; Musical Elements, whereby the value of musical experience shifted with the virtual models; Co-creation through Singing, with an overwhelming sense of loss of the embodied experience of singing together in real-time, which is unattainable from existing virtual choir models. The experiences, activities and reflections of choir singers during lockdown present a unique perspective to understand what makes group singing a meaningful experience for many. Co-creation through Singing needs further investigation to understand the impact of its absence on virtual choirs being able re-create the benefits of in-person choirs.